1993
DOI: 10.1002/jcb.240530415
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of melatonin in different mammalian tissues: Immunocytochemical and radioimmunoassay evidence

Abstract: Melatonin was detected by an improved immunocytochemical technique in the cell nuclei of most tissues studied including several brain areas, pineal gland, Harderian gland, gut, liver, kidney, and spleen from rodents and primates. Cryostat sections from tissues fixed in Bouin's fluid, formalin, or acetone/ethanol were used. The nuclear staining appeared primarily associated with the chromatin. The nucleoli did not exhibit a positive reaction. The melatonin antiserum was used in the range of 1:500 to 1:5,000. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
1
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 298 publications
(170 citation statements)
references
References 32 publications
6
158
1
5
Order By: Relevance
“…Additionally, the lipophilicity of aMT permits that the indoleamine crosses cell membranes, reaching all intracellular structure (Costa et al, 1997;Menendez-Pelaez et al, 1993). In vitro and in vivo experiments have shown that aMT influences mitochondrial homeostasis, reducing mitochondrial hydroperoxide levels and stimulating the activity of GPx and GRd Martin et al, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, the lipophilicity of aMT permits that the indoleamine crosses cell membranes, reaching all intracellular structure (Costa et al, 1997;Menendez-Pelaez et al, 1993). In vitro and in vivo experiments have shown that aMT influences mitochondrial homeostasis, reducing mitochondrial hydroperoxide levels and stimulating the activity of GPx and GRd Martin et al, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Melatonin, being highly lipophilic, readily traverses the blood-brain barrier and the phospholipid bilayer membrane, entering the cellular cytoplasmic and nuclear compartments (Menendez-Pelaez et al, 1993)-an essential prerequisite for any efficacious neuroprotectant. Furthermore, blood-brain barrier disruption is a common consequence of TBI, with blood cells and serum components leaking into the cerebral tissue, initiating a molecular cascade that activates the immune system and inflammatory response (Morganti-Kossmann et al, 2001), providing an additional source for the generation of free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that melatonin concentrations are sufficiently high in lipid-rich membranes as well as in the aqueous cytosol and nucleoplasm to afford significant antioxidative protection. Although not frequently studied, both radioimmunoassay as well as immunocytochemical findings show high levels of melatonin in the nucleus and they generally indicate that intracellular concentrations of melatonin exceed those measured in the blood (68). The reported subcellular distribution is consistent with its high lipid solubility (69) as well as with its ability to dissolve in aqueous media (70).…”
Section: Melatonin As An Antioxidantmentioning
confidence: 80%